2020
DOI: 10.1186/s12879-020-05053-z
|View full text |Cite
|
Sign up to set email alerts
|

Three monthly doses of 60 mg/kg praziquantel for Schistosoma haematobium infection is a safe and effective treatment regimen

Abstract: Background: Praziquantel (PZQ) is the standard treatment for Schistosomiasis in sub-Saharan Africa. However, there is evidence suggesting praziquantel treatment failure in Schistosome infections with associated potential renal impairment. The objective of this study was to determine the effect of three monthly doses of 60 mg/kg/day PZQ on schistosome egg count, liver and renal function during the treatment of urinary schistosomiasis in Ghana. Methods: A nested case-control study was designed from a cohort scre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is because several studies have demonstrated that praziquantel reduced fertility in the Schistosome [ [36] , [37] , [38] , [39] ]. Aside the reduced fecundity imposed on the Schistosome possibly by praziquantel, treatment failure has also been widely reported [ 14 , 19 , 20 ]. Again, egg negative Schistosome could be due to the presence of immature or menopausal worms, presence of all male or all female parasites in the study participants and excretion of eggs on a different day [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because several studies have demonstrated that praziquantel reduced fertility in the Schistosome [ [36] , [37] , [38] , [39] ]. Aside the reduced fecundity imposed on the Schistosome possibly by praziquantel, treatment failure has also been widely reported [ 14 , 19 , 20 ]. Again, egg negative Schistosome could be due to the presence of immature or menopausal worms, presence of all male or all female parasites in the study participants and excretion of eggs on a different day [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several cases of therapeutic failure of praziquantel used for the treatment of schistosomiasis have been reported [ 14 ]. Praziquantel treatment failure in both urinary and intestinal schistosomiasis have been reported in Spain [ 15 ], Italian returnees from Uganda [ 14 ], Senegal [ 16 ], Egypt [ 17 , 18 ], Malawi [ 19 ] and Ghana [ 20 ]. These studies underscore the importance of assessments of the efficacy of praziquantel administration after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A single case–control study, intended to examine the safety of three monthly doses of 60 mg/kg PZQ and their efficacy in reducing the eggs count, also examined the effect of this therapy on kidney function of 28 S. haematobium -infected patients with no renal damage. The study showed improvements of post-treatment organ function (increase of the eGFR) without significant adverse effects [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The number of patients Treatment testsfor schistosomiasis were performed on 450 patientsand the group of patients was divided into three groups, each group 150 patients and each group was given a treatment plan. The first group was given according to the general protocol praziquantel 40 mg per kg as a single dose, which is the most used method of treatment [16] and the results were 40 cases out of 150 patients that were cured and this method of treatment was applied in Egypt through the comprehensive treatment program praziquantel. Before treatment, the prevalence of schistosomiasis in villages ranged from more than 30% to 10% to 20% and after using the treatment the prevalence of treatment decreased to less than 3% [17].…”
Section: Healing Casesmentioning
confidence: 99%